(untitled) (Research, Society and Development, 2021)
Objective: To investigate and correlate the level of CRP and pro-inflammatory cytokines as signs of inflammation and to verify cardiovascular risk in patients with Crohn’s disease. Methods: The study was composed of 36 patients (18 control and 18 case) Results: The analyzes showed serum levels of CRP, IL-10, IFN-γ, IL-8, TNF-α higher in patients with the disease when compared to control group, with significant difference in relation to CRP. It was observed that the mean of 131.12, total cholesterol, 40.85, HDL-c and 76.05, LDL-c for the case group Conclusions: Higher CRP and cytokine levels in the case group suggests that patients with Crohn’s disease has increased cardiovascular risk when compared to people without the disease and other risk factors.